2013
DOI: 10.2481/dsj.wds-046
|View full text |Cite
|
Sign up to set email alerts
|

Digitization of Bromide Paper Records to Extract One-Minute Geomagnetic Data

Abstract: INTRODUCTIONIn the past, geomagnetic field observations were recorded in analog form on photographic paper (Jankowski & Sucksdorff, 1996) with a silver bromide emulsion, known as bromide paper. Up to now, these analog magnetograms have been read only by hand scaling with low time resolution. Many observatories have analog records covering long observation periods (Iyemori, Nose, McCreadie, Odagi, Takeda, Kamei et al., 2005). At Kakioka Magnetic Observatory (KMO) in Japan, records on photographic paper of geoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The photographic papers may induce the uncertainties in the amplitude and timing. Regarding the amplitude, Mashiko et al [] compared differences between the digital data created from the analog magnetograms and data measured by the digital recording magnetometer for 1 min data. They found that the standard deviations of the differences over 10 min intervals (i.e., 10 data points) are ≤0.1 nT and ≤0.2 nT for 82% and 98% of intervals, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The photographic papers may induce the uncertainties in the amplitude and timing. Regarding the amplitude, Mashiko et al [] compared differences between the digital data created from the analog magnetograms and data measured by the digital recording magnetometer for 1 min data. They found that the standard deviations of the differences over 10 min intervals (i.e., 10 data points) are ≤0.1 nT and ≤0.2 nT for 82% and 98% of intervals, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…From the analog magnetograms recorded at Kakioka, Mashiko et al [] created digital data for the period between 1956 and 1975, in which we can find geomagnetic pulsations. In their digitization method, the photographic records are scanned at a resolution of 600 pixels per inch, which is equivalent to a time resolution of approximately 7.5 s per pixel.…”
Section: Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c). We recovered the data from 1969 to 1974 by digitizing the lines on the bromide papers using the method of Mashiko et al (2013), and hereafter, focus on the records in late November in 1973 (Periods I-III) spanning three bromide papers ( Fig. 1c).…”
Section: Datamentioning
confidence: 99%